Operations and supply chain management - Chase, Richard B (McGraw Hill Education (I) Pvt. Ltd, 2014)
Operations and supply chain management / Chase, Richard B. -- New Delhi: McGraw Hill Education (I) Pvt. Ltd, 2014 658.5 C487e14 14th ed No. of Copies : 1